IMPLEMENTASI PROGRAM CSR DARMASISWA CHEVRON RIAU PT. CHEVRON PACIFIC INDONESIA PEKANBARU DALAM MENINGKATKAN KUALITAS PENDIDIKAN - Olza Triyani; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Corporate social responsibility (CSR) is essentially a necessity for corporations to interact with local communities. The corporate need to adapt to gain social benefits from its relationship with the local community is trust. In the implementation of CSR required a culture based on ethics that is adaptive.This study aims to determine the implementation of CSR programs Darmasiswa Chevron Riau PT. Chevron Pacific Indonesia in the field of education, knowing the mechanism of the implementation of the Chevron Riau Darmasiswa CSR program and to know the determinants of the success rate and obstacles of the implementation of Chevron Darmasiswa CSR program. This research uses qualitative research method by using Two Way Asymmetrical Model. Research subjects consisted of 6 informants selected through purposive technique. Data collection is done through observation, interview and documentation. To test the validity of data writers used the method of extension of participation and triangulation.The results of this study show that the implementation of Darmasiwa Chevron Riau Program runs starting from the initial concept of DCR special scholarship program for the best high school students in every district / city in Riau Province. The parties involved in the implementation of the DCR program are Dinas Pendidikan from the provincial to district/city and the Politeknik Caltex Riau. PR plays the role of responsible publication and build networking with the parties who help. DCR program implementation mechanism starts from the socialization stage, then selection of high school students / MA / SMK in each school with the criteria of general champion 1, 2 and 3 in class XII and register on the website. The next stage of written test of academic ability is done at district/city level. Then the announcement of the results of district-level selection in local print media. Participants who qualify are invited for provincial selection. The final stage of the announcement of the winner of DCR and Inauguration. The determinants of the success rate of the program can not be separated from local community support and school participation in 12 districts/cities. There are no significant obstacles in the implementation of the program. There are still schools located in remote areas who do not know the DCR Program.Keywords: Implementation, corporate social responsibility, Darmasiswa Chevron Riau